Direct medical resource utilization associated with osteoporosis‐related nonvertebral fractures in postmenopausal women. (15th January 2013) - Jean, Sonia; Bessette, Louis; Belzile, Étienne L; Davison, K Shawn; Candas, Bernard; Morin, Suzanne; Dodin, Sylvie; Brown, Jacques P
Abstract: The purposes of this study were to assess direct medical resource utilization related to the treatment of nonvertebral osteoporotic fractures within 1 year postfracture and to evaluate whether age impacts resource utilization. A previously‐validated algorithm for physician claims databases identified 15, 327 women aged 50 years or older with incident fracture at nonvertebral osteoporotic sites between January 1, 2004 and December 31, 2005. Administrative databases of the health services available to all residents in Quebec served to study fracture‐related health resource utilization in the year after fracture. Data were linked by a unique personal identifier, creating a longitudinal cohort of all fracture cases for health resource utilization. The proportions of fractures treated by open reduction, closed reduction, immobilization or follow‐up by an orthopedic surgeon (OS) were evaluated. The mean number of claims for consultation with an OS or other clinicians in inpatient and outpatient visits, the hospitalization rate and length of stay (LOS) were assessed. Hip/femur fractures represented the highest rate of resource utilization because the majority of them required surgery (91.1%) and hospitalization (94.5%) with a mean (median) LOS of 39.2 (31) days. However, other nonvertebral fracture types needed significant clinical care related to surgery (27.9%), follow‐up consultation with an OS (77.6%), and hospitalization (27.3% of total LOS). Even pelvic fractures, which often do not require surgical treatment, commanded high resource utilization due to the high hospitalization rate (67.4%) with mean (median) LOS of 34.2 (26) days. Moreover, age was an important determinant of health resource utilization, being associated with an increased number of visits to other physicians, hospitalization, and length of hospitalization (LOS), admissions to long term care (LTC), and death. Osteoporosis‐related fractures accounted for substantial healthcare resource utilization. With an aging population and increased prevalence of fractures, strategies for osteoporosis management need to be introduced to reduce the healthcare burden. © 2013 American Society for Bone and Mineral Research